2019
DOI: 10.1038/s41598-019-53917-5
|View full text |Cite
|
Sign up to set email alerts
|

ctDNA detected by ddPCR reveals changes in tumour load in metastatic malignant melanoma treated with bevacizumab

Abstract: Bevacizumab is included in an increasing number of clinical trials. To find biomarkers to predict and monitor treatment response, cancer and angiogenesis relevant mutations in tumour and circulating tumour DNA (ctDNA) were investigated in 26 metastatic melanoma patients treated with bevacizumab. Patients with >1% BRAF/NRAS ctDNA at treatment start had significantly decreased progression free survival (PFS) and overall survival (OS) (PFS: p = 0.019, median 54 vs 774 days, OS: p = 0.026, median 209 vs 1064 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 59 publications
(68 reference statements)
3
35
0
Order By: Relevance
“…For PFS, 5 studies reported adjusted HR by multivariable analysis [ 11 , 13 , 14 , 16 , 17 ] and 2 studies reported unadjusted HR for univariate analysis [ 15 , 18 ] was performed and a significant prognostic effect was confirmed in the analysis of studies that collected ctDNA at baseline (multivariable: HR = 2.68, 95% CI 1.77–4.06, p < 0.001; univarible: HR = 3.27, 95% CI 1.54–6.96, p = 0.002). Obvious heterogeneity was not observed in multivariate PFS ( I 2 = 21.4%, p = 0.278) or univariate OS ( I 2 = 0%, p = 0.363) ( Fig.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For PFS, 5 studies reported adjusted HR by multivariable analysis [ 11 , 13 , 14 , 16 , 17 ] and 2 studies reported unadjusted HR for univariate analysis [ 15 , 18 ] was performed and a significant prognostic effect was confirmed in the analysis of studies that collected ctDNA at baseline (multivariable: HR = 2.68, 95% CI 1.77–4.06, p < 0.001; univarible: HR = 3.27, 95% CI 1.54–6.96, p = 0.002). Obvious heterogeneity was not observed in multivariate PFS ( I 2 = 21.4%, p = 0.278) or univariate OS ( I 2 = 0%, p = 0.363) ( Fig.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…BRAF mutations account for the vast majority of melanomas, followed by NRAS, TERT promoter and other specific gene mutations [ 13 , 15 , 33 , 34 ]. There are also references in the literature that gene mutations in melanoma patients are related to drug resistance, such as BRAFV600E and NRASQ61K mutations [11] . Majority of studies regard great clinical significance of BRAF V600 specific mutation in ctDNA of melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the detection of central nervous system (CNS) tumor hotspot mutations and molecular markers within the cerebrospinal fluid (CSF) of patients has been accomplished with high sensitivity and specificity [ 9 , 10 , 11 , 12 ], the detection of these targets in plasma has been difficult due to lower levels of circulating tumor nucleic acids, including cell-free DNA (cfDNA) and tumor-associated EV RNA (exRNA) [ 13 ]. In patients with primary cancers outside the CNS, liquid biopsy assays have been developed for the diagnosis and monitoring of several cancers, including malignant melanoma, colorectal cancer and prostate cancer [ 8 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%